Морфологія чашечки (calyx) як додаткова діагностична ознака видів роду Nepeta L. - Kovtun-Vodyanitska, S.M. (M.M. Gryshko National Botanical Garden of the NAS of Ukraine, 2010)
The results of original study of morphological peculiarity calyx of samplers of 16 species and one diversity of genus Nepeta L. are presented.